2015
DOI: 10.1016/j.virol.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Two cellular microRNAs, miR-196b and miR-1290, contribute to HIV-1 latency

Abstract: Understanding the mechanism of HIV-1 latency is crucial to the viral reservoir eradication. Human cellular miRNAs can modulate HIV-1 expression by targeting of viral RNAs or host gene transcripts. To identify miRNAs modulating HIV-1 latency, we determined the miRNA expression profiles of HIV-1 latently infected and productively infected cells by microarray and qRT-PCR. Among the differentially expressed miRNAs, miR-196b and miR-1290 targeted the 3' untranslated region of HIV-1 and affected its expression. Ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…YA cells and C11 cells, which are HIV-1-infected or latently infected Jurkat T cells, respectively, were first created in our laboratory and are now used widely in the research community 36, 37, 51, 52, 53, 54. The C11 and YA cells were maintained in RPMI 1640 medium supplemented with 10% (v/v) fetal bovine serum (Gibco), 100 U mL −1 penicillin, and 100 μg mL −1 streptomycin (Invitrogen) at 37°C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…YA cells and C11 cells, which are HIV-1-infected or latently infected Jurkat T cells, respectively, were first created in our laboratory and are now used widely in the research community 36, 37, 51, 52, 53, 54. The C11 and YA cells were maintained in RPMI 1640 medium supplemented with 10% (v/v) fetal bovine serum (Gibco), 100 U mL −1 penicillin, and 100 μg mL −1 streptomycin (Invitrogen) at 37°C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Whisnant et al (2013) [ 222 ] tested the primary CD4 + PBMCs 3 days post infection, because, as they reason in their report, the HIV-1-infected T cells in vivo have a half-life of only around 24 h [ 227 ]. By comparing the miRNA expression profiles of cells productively or latently infected by HIV-1, Wang et al [ 224 ] identified two cellular miRNAs- miR-196b and miR-1290, that were relatively upregulated in latently infected cells. These two miRNAs were also shown to directly target the 3′UTR of HIV-1 transcripts, while overexpression and knockdown experiments conducted using lab cell lines and CD4 + T-cells from HIV-1-infected patients receiving cART revealed the potential of these miRNAs to modulate HIV-1 replication, as evidenced by changes in virus production and infectivity.…”
Section: Cellular Mirnas As Anti-viral Factors In Hiv-1 Replicatiomentioning
confidence: 99%
“…C11 cells are a type of HIV-1 latently infected cells constructed by our lab. 8 , 27 , 28 , 29 , 30 , 31 , 32 YA were derived from Jurkat T cells infected with HIV-1 pseudovirus carrying the eGFP reporter gene. 8 , 27 Both of them were cultured in RPMI 1640 medium with 10% FBS (Gibco, Grand Island, NY, USA), 100 U/mL penicillin, and 100 μg/mL streptomycin (Invitrogen, Shanghai, China) at 37°C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%